Paradoks Konsumsi Kopi Terhadap Risiko Kejadian Stroke: Sebuah Kajian Sistematis - Gunawan, Andi Muh. Aunul Khaliq; Khairunnisa, Indah Nurul; Fais, Muthia Kintan (Talenta Publisher, 2021)
Background: Coffee is one of the drinks most often consumed throughout the world and is the second most popular beverage in the world after water. At present, the effect of coffee consumption on the human body is increasingly being studied, especially on the cardiovascular system. Many studies say that coffee consumption can prevent stroke, either directly or indirectly against stroke risk factors by a variety of mechanisms caused by the compounds contained in coffee. However, to date various prospective studies looking at the relationship between coffee consumption and stroke risk are still inconsistent. Objectives: To determine the relationship of coffee consumption with the risk of stroke. Methods: We searched on MEDLINE and PubMed, using the keywords â€œcoffeeâ€ or â€œcaffeineâ€ and